Short-Term Outcomes of Dorsal Wrist Ganglion Excision: Is What We Are Doing Working? - Bandzaite, Laima; Hoogendam, Lisa; Greminger, Martina; Koopman, Jaimy E.; Kooij, Yara E. V.; Smit, Jeroen; Selles, Ruud W.; Slijper, Harm P.; the Supexor Group; the Hand-Wrist Study Group; Calcagni, Maurizio (Journal of Wrist Surgery, 2025)
This study aimed to describe patient-reported pain and hand appearance 3 months following dorsal wrist ganglion excision. The secondary aims were to evaluate return to work (RTW), satisfaction with treatment, recurrence, and complications.We included 1,000 patients who had a dorsal wrist ganglion excision in a specialized center for hand and wrist disorders and completed the relevant questionnaires preoperatively. Six hundred and fifty-nine patients who also completed all relevant questionnaires 3 months postoperatively were included for the primary analysis. Data on complications and recurrence were available from patients' records for all 1,000 patients and were scored following the International Consortium of Healthcare Outcomes Complications in Hand and Wrist (ICHAW) conditions tool.Most patients (63%) experienced clinically relevant improvement in pain following dorsal wrist ganglion excision. Hand appearance improved, and 87% of the patients rated their satisfaction with treatment results as fair to excellent. Median time to RTW was 3 weeks. Any deviation from expected recovery according to the ICHAW definition was noted for 111 patients (11%), with most being minor adverse protocol deviations. Nine patients (9/111, 8%; 9/1,000, 0.9%) experienced a Grade 3 complication (e.g., complex regional pain syndrome or condition requiring additional surgery). During a median follow-up of 4.7 years, 104 patients (10.4%) had a recurrence of the dorsal wrist ganglion.This study found that open excision of dorsal wrist ganglia leads to clinically relevant pain reduction and good satisfaction in most cases. However, there was a relatively high variability in outcomes. Complication and recurrence rates were comparable to other studies and remained fairly high. It is important to consider and elaborate this to patients preoperatively to address their expectations and make an informed, consensual decision regarding the treatment.Therapeutic, Level II.
Keywords: ganglion cysts; wrist; dorsal; open ganglion excision; patient-reported outcome measures; short-term outcomes